Clinical outcomes in patients with nonfunctioning pituitary adenomas managed conservatively. (12th August 2015) - Sam, Amir H.; Shah, Sachit; Saleh, Keenan; Joshi, Jay; Roncaroli, Federico; Robinson, Stephen; Cox, Jeremy; Martin, Niamh M.; Mendoza, Nigel; Meeran, Karim; Mehta, Amrish; Dhillo, Waljit S.
Summary: Context: The natural history and the optimum management of patients with nonfunctioning pituitary adenomas (NFPAs) are unclear. Objective: Our objective was to characterize the natural history of patients with NFPAs managed conservatively. Design and patients: We conducted a retrospective analysis of patients presenting to a tertiary referral centre between 1986 and 2009. Patients with pituitary adenomas and no clinical or biochemical evidence of hormonal hypersecretion were included. Those presenting with apoplexy or a radiological follow‐up period of less than 1 year were excluded. The pituitary imaging for all patients was re‐examined by two neuroradiologists in consensus. Outcome measures: The outcome measures were change in tumour size and pituitary hormone function. Results: Sixty‐six patients were managed conservatively for a mean follow‐up period of 4·3 years (range: 1–14·7). Forty‐seven (71%) had a macroadenoma, and nineteen (29%) had a microadenoma. Tumour size decreased or remained stable in 40% of macroadenomas and 47% of microadenomas. The median annual growth rate of enlarging macroadenomas and microadenomas was 1·0 mm/year and 0·4 mm/year, respectively. The median annual growth rate of macroadenomas was significantly higher than that of microadenomas ( P < 0·01). Sixty‐eight percentage of patients with a macroadenoma had pituitary hormone deficiency in one or more axes, compared to 42% of those with a microadenoma. Conclusion: Patients with NFPAs without optic chiasm compression can be managed conservatively. All patients need pituitary function assessment, irrespective of tumour size. These findings provide clinically relevant data for the management of patients with NFPAs.